The Effect of Flashsale and Price Discounts on Impulsive Buying (Study on Lazada Application User Students at the University of North Sumatra) - Setia F Sihaloho (Journal Boas : Business, Economics, Accounting And Management, 2022)
Shopping online is one of the conveniences in meeting the needs of life in today's modern lifestyle. There are many conveniences obtained when making purchases online. And members make it easy and can save time and energy because they don't have to go to the store but can get the desired product through what is given. This study aims to analyze how the effect of Flashsale and price discounts on Impulsive Buying of students using the Lazada application at the University of North Sumatra. The effect of the related variables, namely flash sale and price discounts, will be analyzed partially and simultaneously on the increase in Impulsive Buying. This research uses quantitative research with an associative approach. The sample taken in this study was 100 people who were taken by purposive sampling technique. Primary data in this study were obtained from distributing questionnaires and secondary data obtained through the literature study. The analytical method used is validity test, classical assumption test, reliability test, multiple linear regression analysis and hypothesis testing obtained using SPSS 22 software. The results of the research conducted showed that the variable Flashsale (X1) had a significant effect on Impulsive Buying. And the price discount variable (X2) has a significant effect on Impulsive Buying, variables Flashsale and price discounts simultaneously affect Impulsive Buying. Based on the coefficient of determination test, there is a fairly close relationship between Flashsales and price discounts on Impulsive Buying with an R value of 0.893. Through the value of R square there is acontribution Flashsale and a price discount of 79. 8% to Impulsive Buying. While the remaining 20.2% is influenced by other variables that are not explained in this study.